A 21-year record of vertically migrating subepilimnetic populations of Cryptomonas spp. Issue 2 (1st January 2016) - deNoyelles, Frank; Smith, Val H.; Kastens, Jude H.; Bennett, LeeAnn; Lomas, John M.; Knapp, Charles W.; Bergin, Sean P.; Dewey, Sharon L.; Chapin, Bridgett R. K.; Graham, David W.
Abstract: The vertical distribution and diel migration of Cryptomonas spp. were monitored continuously for 21 years in mesotrophic Cross Reservoir, northeast Kansas, USA. The movements of these motile algae were tracked on multiple dates during July–October of each year using in situ fluorometry and optical microscopy of Lugol's iodine-preserved samples. Episodes of subepilimnetic diel vertical migration by Cryptomonas were detected and recorded on 221 different days between 1994 and 2014, with just 2 of these years (1998 and 2013) lacking any sampling events with deep peaks sufficiently large enough to track. Whenever a subepilimnetic layer of Cryptomonas was detectable, it was generally observed to ascend toward the bottom of the epilimnion beginning approximately at sunrise; to descend toward the lake bottom during the late afternoon and evening; and to remain as a deep-dwelling population until dawn of the following day. Moreover, there was high day-to-day consistency in the absolute water column depths at which the migrating algal cells would cease their ascending or descending movement. We believe this unique and remarkable dataset comprises the most detailed record of diel migratory behavior for any planktonic freshwater alga reported for a single freshwater lake.